EVALUASI PROGRAM JAMINAN KESEHATAN NASIONAL (STUDI EVALUASI PROGRAM BPJS KESEHATAN PADA TENAGA KERJA DI SURABAYA TAHUN 2014-2016) - Aninda Yusmiati Dewi; Sjamsiar Sjamsudin; Lely Indah Mindarti (Yogyakarta State University, 2017)
Law Number 24 Year 2011 on Social Security Administering Institution functions as guidance in the implementation of social insurance. One of the membership requirement mentioned in the act is the workforce (PPU). To obtain the Health Insurance, the Manpower (PPU) is required to pay a contribution of 5% of the Regional Minimum Wage under the terms of 4% of employers and 1% of Labor. Nevertheless the expected health services have not been achieved yet. The needs for evaluating National Health Insurance program were to assess the extent of program effectiveness, service improvement and membership expansion. This research focused on input, process, and output of JKN Program implementation operated by BPJS Health KCU Surabaya. The research used descriptive qualitative method. The results showed that the assessment of the JKN program implementation both in terms of input, process and output has been implemented quite well.Keywords: Policy Evaluation, National Health Insurance Program, BPJS on Health Surabaya, and Manpower